A Kineño remembers : from the King Ranch to the White House - Cavazos, Lauro (Perspectives on south Texas., 2006)
On September 20, 1988, Lauro Cavazos became the first Hispanic in the history of the United States to be appointed to the Cabinet, when then-vice president George H.W. Bush swore him in as secretary of education. Cavazos, born on the legendary King Ranch in South Texas and educated in a two-room ranch schoolhouse, served until December 1990, after which he returned to his career in medical education and academic administration.